STUDY OF RAISED ALANINE AMINOTRANSFERASE IN PATIENTS OF TYPE 2 DIABETES MELLITUS: Raised Alanine Aminotransferase in type 2 Diabetes Militus - Ahmed, Shahid; Ali, Nadir; Abdullah, Zafar; Ilyas, Mohammad; Naeem, Uzma (Pakistan Armed Forces Medical Journal, 2008)
Objective: The aim of the study was to determine frequency of fatty liver, hepatitis C and hepatitis B in type 2 diabetes with raised ALT in our population.Study Design: This was a descriptive study.Place and Duration: Study has been carried out at medical out patient clinic in CMH Malir, over a span of one year (2005-2006).Patients and Methods: We studied patients of type 2 diabetes who had persistently raised serum ALT (alanine aminotransferases) for more than eight weeks. In medical out-patient clinic, 101 patients of type 2 diabetes with raised serum ALT were studied.  Age, sex, BMI (body mass index) and duration of diabetes were recorded and blood was tested for plasma fasting glucose, triglycerides, cholesterol, anti HCV antibodies and HBsAg. Ultrasonography of upper abdomen was done in all patients to look for liver size, fatty liver or any evidence of chronic liver disease.Results: Results showed positive association of raised ALT in type 2 diabetic patients with high body mass index, recent onset diabetes, fatty liver, raised triglycerides and poorly controlled diabetes. About 22% of the studied patients were positive for hepatitis C.Conclusion: Mild to moderate elevation in serum ALT is commonly encountered in patients of type 2 diabetes mellitus. Most of these individuals are overweight and/or have fatty liver on ultrasonography.